Harmonizacja podatków bezpośrednich w Polsce w świetle dyrektyw Unii Europejskiej - Nowak, Anna (The harmonization of direct taxes in Poland in the light of EU directives, 2006)
The author makes a short analysis of direct taxes harmonization effects. She discusses the most important EU directives in the field of discussed harmonization and also often refers to the Polish tax law. She points further adapt processes directions. The author pays attention to the complex handling of fiscal adaptation and possible threats connected with it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 242-249